2006
DOI: 10.1016/j.expneurol.2006.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Glial activation in white matter following ischemia in the neonatal P7 rat brain

Abstract: This study examines cell death and proliferation in the white matter after neonatal stroke. In post-natal day 7 injured rat, there was a marked reduction in myelin basic protein (MBP) immunostaining mainly corresponding to numerous pyknotic immature oligodendrocytes and TUNEL-positive astrocytes in the ipsilateral external capsule. In contrast, a substantial restoration of MBP, as indicated by the MBP ratio of left-toright, occurred in the cingulum at 48 (1.27 ± 0.12) and 72 (1.30 ± 0.18, p<0.05) hours of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 45 publications
6
45
1
Order By: Relevance
“…In this regard, studies of astroglial cell death after different types of acute injuries such as traumatic brain injury (Beer et al, 2000;Newcomb et al, 1999) and ischemia/ excitotoxicity (Biran et al, 2006;Dihne et al, 2001), have shown that apoptosis occurs only in few astrocytes, in agreement with our findings in the injured neonatal brain. Alternatively, non-apoptotic roles of caspase-3 need to be considered.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, studies of astroglial cell death after different types of acute injuries such as traumatic brain injury (Beer et al, 2000;Newcomb et al, 1999) and ischemia/ excitotoxicity (Biran et al, 2006;Dihne et al, 2001), have shown that apoptosis occurs only in few astrocytes, in agreement with our findings in the injured neonatal brain. Alternatively, non-apoptotic roles of caspase-3 need to be considered.…”
Section: Discussionsupporting
confidence: 91%
“…We next analyzed the white matter underlying cortical stroke in both the cingulum and external capsule (Fig. 3), where cell damage has been previously reported (19). Melatonin treatment was associated with a significant decrease in the density of TL-positive cells in the cingulum (by 30%, p Ͻ 0.05) and external capsule (by 40%, p Ͻ 0.05) when compared with vehicle-treated animals ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We previously developed a neonatal model of stroke in 7-d-old (P7) rat characterized by apoptotic cell death (16,17), inflammatory responses (18,19), and oxidative stress (20). In addition to cerebral infarct, this model induced glial activation in underlying white matter including persistent activation of microglia and astrogliosis (19,21). As the presence of activated microglia is known to impair the oligodendroglial lineage, we hypothesized that melatonin could be used as an effective neuroprotectant in this stroke model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coronal section, 5 μm-thick, were used for staining, immunohistochemistry (IHC) and immunofluorescence (IF), as previously described by Girard et al (2009). Primary antibodies (Abs) included Abs directed against: glial fibrillary acid protein (GFAP; 1:500, Chemicon, ON, Canada; Ferrucci et al, 2010;Girard et al, 2009), ionized calcium binding adapter molecule 1 (Iba-1; 1:500, Wako Chemicals, VA, US; Faustino et al, 2011;Girard et al, 2009), proliferating cell nuclear antigen (PCNA; 1:500, Santa Cruz Biotechnology, CA, US; Girard et al, 2010b), myelin basic protein (MBP; 1:500, Chemicon, ON, Canada; Biran et al, 2006;Girard et al, 2009), doublecortin (DCX, 1:500, Abcam MA, US; Geoghegan and Carter, 2008) and neuronal nuclei (NeuN, 1:100, Millipore, MA, US; Liew et al, 2012). After washing, sections were incubated with the appropriate secondary Ab: anti-mouse-HRP (1:100, Santa Cruz Biotechnology, CA, US) or anti-rabbit-HRP (1:100, Serotec, NC, US) for IHC, and anti-mouse, anti-chicken or antirabbit alexa fluoconjugated (1:500, Invitrogen, ON, Canada) for IF.…”
Section: Brain Histological Analysismentioning
confidence: 99%